2021
DOI: 10.1111/bjhp.12565
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of palliative care professionals and their responses to work‐related stress: A qualitative study

Abstract: Objectives Previous qualitative research has demonstrated that palliative care professionals (PCPs) deal with a wide array of emotionally challenging issues associated with the care they provide. Although previous research has identified self‐care strategies PCPs engage in, there is a lack of focus on what responses are helpful and/or unhelpful. The aim of the current study is to understand and describe the experiences of PCPs and to explore the helpful and unhelpful responses to work‐related stress they emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…As practical implications, the need for offers for stress reduction [ 56 ] such as supervision, quality circles [ 19 ], stress management training [ 24 , 57 ], and collegial case consultation (intervision) [ 19 ] can be deduced. According to our data, especially female GPs and physicians with more professional experience can benefit from this, while access to such offers should be open to all GPs regardless of the level of qualification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As practical implications, the need for offers for stress reduction [ 56 ] such as supervision, quality circles [ 19 ], stress management training [ 24 , 57 ], and collegial case consultation (intervision) [ 19 ] can be deduced. According to our data, especially female GPs and physicians with more professional experience can benefit from this, while access to such offers should be open to all GPs regardless of the level of qualification.…”
Section: Discussionmentioning
confidence: 99%
“…PC-related job stress factors of GPs are not well researched. Most studies about job stress factors of PC providers focus on inpatient settings and mostly but not exclusively on specialised PC facilities and wards [ 11 , 23 , 24 , 25 ]. We hypothesise that GPs with lower PC qualifications perceive PC-related job stress factors as more burdensome because they are less well trained [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The intervention will cover key ACT processes including being present, finding purpose, perspective taking and engaging in life values (Table 1). The content has been informed by previous interventions delivered by the team for health professionals in other settings, as well as research on occupational stress, wellbeing, self-compassion and resilience in palliative care 3,15,[25][26][27][28] . The content is described in a draft manual, which will be revised and shared on the ISRCTN registry on completion of the study.…”
Section: Intervention Design and Contentmentioning
confidence: 99%
“…Palliative care work is generally viewed as rewarding, bringing meaning, and purpose to professional care staff. [1][2][3] However, alongside positive experiences, stress, distress and burnout are common. [4][5][6] Some stressors are typical of those identified across healthcare settings such as unmanageable workloads, shift work, staff shortages and lack of training on specific issues.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research identified common responses to workplace stressors in palliative care staff including emotional suppression, over-identification with patient suffering, and neglect of self-care behaviours. 2,6 These kinds of responses are typically targetted by Acceptance and Commitment Therapy. Acceptance and Commitment Therapy is efficacious in treating stress, anxiety and depression in a broad range of populations, including occupational contexts where emotional labour is high.…”
Section: Introductionmentioning
confidence: 99%